Factors associated with cognitive and communication delay in children aged 0 to 3 years using the Battelle-Developmental Inventory, 2nd edition - Florentina Febrina; Veronika Cendana Pinasthika Lawalata; Yetty Ramli (Indonesian Pediatric Society, 2023)
Background The first years of life are crucial in cognitive and communication development. Delayed functional development impedes children’s future academic and occupational performance. Therefore, early detection is important for effective resolution in order to minimize further impairment. Objective To evaluate cognitive and communication developmental delay in children under 3 years of age in Jakarta using the Battelle Developmental Inventory, 2nd edition (BDI-2). Methods A cross-sectional study was conducted in Jakarta in 2020, including children aged under 3 years of age without chronic medical conditions that hinder cognitive and speech function. We collected subjects’ demographic characteristics, evaluated their communication and cognitive development using the BDI-2, and analyzed for risk factors of delays. Results Of 121 children, 34 (28.1%) had cognitive delay and 21 (17.4%) had communication delay. Bivariate analysis revealed that male gender (P=0.048) and non-exclusive breastfeeding (P=0.003) were significantly associated with communication delay, while only male gender was associated with cognitive delay (P=0.015). Multivariate analysis revealed that significant risk factors for communication delay were male gender (P=0.043) and non-exclusive breastfeeding (P=0.023). Conclusion Male gender and non-exclusive breastfeeding are significant risk factors for delayed communication development, and only male gender was a significant risk factor for cognitive delay. Socioeconomic status, primary caregiver, and breastfeeding duration, were not found to be risk factors for delays.